An Autophagy-Independent Role for ATG41 in Sulfur Metabolism During Zinc Deficiency. Issue 3 (1st March 2018) - Bucci, Michael D; Weisenhorn, Erin; Haws, Spencer; Yao, Zhiyuan; Zimmerman, Ginelle; Gannon, Molly; Taggart, Janet; Lee, Traci; Klionsky, Daniel J; Russell, Jason; Coon, Joshua; Eide, David J
Abstract: The Zap1 transcription factor of Saccharomyces cerevisiae is a key regulator in the genomic responses to zinc deficiency. Among the genes regulated by Zap1 during zinc deficiency is the autophagy-related gene ATG41 . Here, we report that Atg41 is required for growth in zinc-deficient conditions, but not when zinc is abundant or when other metals are limiting. Consistent with a role for Atg41 in macroautophagy, we show that nutritional zinc deficiency induces autophagy and that mutation of ATG41 diminishes that response. Several experiments indicated that the importance of ATG41 function to growth during zinc deficiency is not because of its role in macroautophagy, but rather is due to one or more autophagy-independent functions. For example, rapamycin treatment fully induced autophagy in zinc-deficient atg41 Δ mutants but failed to improve growth. In addition, atg41 Δ mutants showed a far more severe growth defect than any of several other autophagy mutants tested, and atg41 Δ mutants showed increased Heat Shock Factor 1 activity, an indicator of protein homeostasis stress, while other autophagy mutants did not. An autophagy-independent function for ATG41 in sulfur metabolism during zinc deficiency was suggested by analyzing the transcriptome of atg41 Δ mutants during the transition from zinc-replete to -deficient conditions. Analysis of sulfur metabolites confirmed that Atg41 is needed for the normal accumulation of methionine, homocysteine, and cysteine in zinc-deficient cells. Therefore, we conclude that Atg41 plays roles in both macroautophagy and sulfur metabolism during zinc deficiency.